Interdisciplinary mixed methods systematic reviews: Reflections on methodological best practices, theoretical considerations, and practical implications across disciplines. Issue 1 (2022) - Nowell, Lorelli; Paolucci, Alessandra; Dhingra, Swati; Jacobsen, Michele; Lorenzetti, Diane L.; Lorenzetti, Liza; Oddone-Paolucci, Elizabeth
Abstract: Literature reviews have recently gained increased recognition for their value in advancing knowledge and decision making across disciplines. While interdisciplinary mixed-methods systematic reviews create opportunities to synthesize knowledge and insights from across disciplines, it is important to highlight the challenges, successes, and theoretical and practical considerations in combining research from various disciplines and research methodologies. In this article, we reflect on our experiences with conducting an interdisciplinary mixed-methods systematic review and outline theoretical and practical considerations involved in ensuring that methodologically rigorous, transparent, and meaningful research was achieved. As a group of academics from Education, Medicine, Nursing, and Social Work, who worked together on an interdisciplinary mixed-methods systematic review, we offer insights from our personal experiences as a transparent exemplar for how we embraced the challenges in conducting our project and managed the bottlenecks that often occur in interdisciplinary research. Highlights: Interdisciplinary mixed-methods systematic reviews are a novel method for synthesizing knowledge from across disciplines. There are important theoretical and practical considerations for conducting rigorous interdisciplinary mixed-method systematic reviews. Literature that focuses on the learnings of interdisciplinarity can advance the effectiveness and impact of interdisciplinary research.